2019
DOI: 10.1007/s10584-019-02447-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender in climate change, agriculture, and natural resource policies: insights from East Africa

Abstract: Gender mainstreaming was acknowledged as an indispensable strategy for achieving gender equality at the 1995 Beijing Platform for Action. Since then, governments have made substantial efforts in developing gender-responsive policies and implementation strategies. The advent of climate change and its effects, which have continued to impact rural livelihoods and especially food security, demands that gender mainstreaming efforts are accelerated. Effective gender mainstreaming requires that gender is sufficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 24 publications
5
41
1
Order By: Relevance
“…With a focus on East Africa, and using the same framework as Gumucio and Tafur Rueda (2015), Ampaire et al (2020) examined the extent to which gender issues were integrated and budgeted for in 155 climate change, environmental, and agriculture policies in Tanzania and Uganda. Their study also found increasing integration of gender dimensions in policy in both countries, although they discovered certain disharmonies across governance levels; an insufficient attention to structural causes of gender inequality, with gender issues often being equated to 'women's issues'; and limited budget allocations for gender (if at all) that varied across the different financial years analysed.…”
Section: National Climate Policy: Rhetoric or Action?mentioning
confidence: 99%
See 2 more Smart Citations
“…With a focus on East Africa, and using the same framework as Gumucio and Tafur Rueda (2015), Ampaire et al (2020) examined the extent to which gender issues were integrated and budgeted for in 155 climate change, environmental, and agriculture policies in Tanzania and Uganda. Their study also found increasing integration of gender dimensions in policy in both countries, although they discovered certain disharmonies across governance levels; an insufficient attention to structural causes of gender inequality, with gender issues often being equated to 'women's issues'; and limited budget allocations for gender (if at all) that varied across the different financial years analysed.…”
Section: National Climate Policy: Rhetoric or Action?mentioning
confidence: 99%
“…From the previous sections, it is clear that the increasing threats posed by climate change and global environmental degradation to rural communities, particularly to people who are vulnerable, will require more effective gender equality and inclusion approaches. However, even though gender mainstreaming has been introduced in climate policy around the globe, it has produced limited results in tackling gender inequalities (Ampaire et al 2020). Critics claim that inadequate progress to date has been due partly to a disproportionate focus on addressing 'gender symptoms' rather than on the causes of gender inequalities (AAS 2012;FAO et al 2019).…”
Section: Towards Gender Equality In Climate Policymentioning
confidence: 99%
See 1 more Smart Citation
“…We interrogate perceived causes of gender inequalities and proposed local prescriptions for translating these into policy, and we examine the extent to which different global and local norms are mobilised in their understandings of gender equality. Uganda presents an interesting case to investigate these issues because the apparent dominance of gender equality in agriculture and climate change policy documents, largely informed by global discourses, is often met with policy inaction (Acosta et al 2019a;Ampaire et al 2020). In such contexts, would considering locally proposed solutions help to identify more effective strategies?…”
Section: Introductionmentioning
confidence: 99%
“…Even though different approaches and methods have been developed to assess CC and FSN issues (Ampaire et al, 2017;CEPAL, 2018), and to assess gender and CC issues (Gumucio and Tafur, 2015;Bryan et al, 2016;Kristjanson et al, 2017;Acosta et al, 2019aAcosta et al, , 2020Ampaire et al, 2020), considerably less attention has been devoted to methodologies and frameworks that assess gender and food insecurity issues in policies and interventions. As explained by Bryan et al (2017a) gender and nutrition issues are rarely addressed in the resilience literature.…”
Section: Introductionmentioning
confidence: 99%